(untitled) (Journal of the College of Basic Education, 2023)
Perhaps the first thing a researcher encounters in Umayyad poetry is that praise poems occupy a large space.And that most of these poems are addressed to those with power and prestige, including caliphs, governors, and wealthy people.Most of the praise poetry the poets took from it as a means of material gain, or to draw closer to the caliphs.the Umayyads, especially if we know that the Umayyad caliphs were well aware of the importance of poetry and its roleIn the life of the Arabs, that is why they tried to buy off the debts of poets with their money, so that their reputation would spread among the Arabs.Perhaps the first caliph, Muawiyah bin Abi Sufyan, was the one who enacted this rule for the caliphs who came after him.Sunnah that became a tradition followed by the Umayyad caliphs. Dr. Youssef referred to thisKhalif said: “The matter was not set right for Muawiya until Damascus became the capital of the new state.